2022
DOI: 10.1186/s12916-021-02209-9
|View full text |Cite
|
Sign up to set email alerts
|

The anti-aging factor Klotho protects against acquired long QT syndrome induced by uremia and promoted by fibroblast growth factor 23

Abstract: Background Chronic kidney disease (CKD) is associated with increased propensity for arrhythmias. In this context, ventricular repolarization alterations have been shown to predispose to fatal arrhythmias and sudden cardiac death. Between mineral bone disturbances in CKD patients, increased fibroblast growth factor (FGF) 23 and decreased Klotho are emerging as important effectors of cardiovascular disease. However, the relationship between imbalanced FGF23-Klotho axis and the development of card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 101 publications
2
10
0
Order By: Relevance
“…69 Furthermore, we found that administration of sKL protects a mouse model of CKD from developing ventricular arrhythmias. 79 Combined, these studies indicate that sKL can directly inhibit the pathologic actions of FGF23 on cardiac myocytes, suggesting the potential for sKL administration as a novel cardioprotective therapy that might be effective in scenarios of systemic FGF23 elevations, such as CKD. However, attempts from various groups to purify sKL protein in larger amounts have failed, and sKL protein appears to be highly unstable.…”
Section: Results Skl Promotes Fgf23 Binding To Various Fgfr Isoformsmentioning
confidence: 88%
See 1 more Smart Citation
“…69 Furthermore, we found that administration of sKL protects a mouse model of CKD from developing ventricular arrhythmias. 79 Combined, these studies indicate that sKL can directly inhibit the pathologic actions of FGF23 on cardiac myocytes, suggesting the potential for sKL administration as a novel cardioprotective therapy that might be effective in scenarios of systemic FGF23 elevations, such as CKD. However, attempts from various groups to purify sKL protein in larger amounts have failed, and sKL protein appears to be highly unstable.…”
Section: Results Skl Promotes Fgf23 Binding To Various Fgfr Isoformsmentioning
confidence: 88%
“…Several studies have shown that elevated sKL levels in animal models of CKD have cardioprotective effects. 54,56,58,78,79 A recent study suggests that these effects are independent of sKL's antihypertensive effects and are rather based on the direct actions of sKL on the heart. 80 To determine whether sKL interferes with the direct effects of FGF23 on cardiac myocytes, we treated isolated NRVMs with FGF23 for 48 hours, which induced hypertrophic growth as determined by an increase in the area of immunolabeled cells (Figure 2a), as shown before.…”
Section: Results Skl Promotes Fgf23 Binding To Various Fgfr Isoformsmentioning
confidence: 99%
“…These opposite results could be explained by the fact that the relation between kidney function and soluble klotho is not closely linear, depending on the time in which klotho is measured after AKI. At the cardiac level, there is evidence that klotho exerts a cardioprotective role, since its deficit is linked to uremic cardiac remodelling [ 40 ] and its exogenous supplementation protects the cardiac function [ 18 , 24 ]. Here, we demonstrated that a partial klotho deficiency that occurs with any evidence of renal disease, could have an added deleterious impact in the setting of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that several uremic experimental models develop a cardiac failure phenotype with relevant cardiomyocyte alterations including contractile dysfunction and intracellular calcium (Ca 2+ ) mishandling [ 18 , 19 , 20 , 21 ]. In this uremic cardiomyopathy setting, klotho has emerged as a new therapeutic target to protect cardiac function by normalising intracellular Ca 2+ handling in ventricular cardiomyocytes, where endogenous klotho overexpression or increasing its bioavailability exogenously through recombinant murine klotho administration improves cardiomyocyte function and impedes deleterious cardiac remodelling associated with renal damage [ 20 , 22 , 23 , 24 ]. On the other hand, a severe klotho deficiency, as happens in hypomorphic kl/kl mice, significantly worsens cardiomyocyte function, inducing a deleterious ionic remodelling that predisposes them to suffer heart failure and fatal ventricular arrhythmias even in the absence of any additional renal insult [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation